Trends in household debt and credit - Andrew Haughwout; Donghoon Lee; Joelle Scally; Lauren Thomas; Wilbert van der Klaauw (Federal Reserve Bank of New York, 2019)
Since the onset of the 2008 financial crisis, consumer financial and borrowing behavior, once considered a relatively quiet little corner of finance, has been of enormously increased interest to policymakers and researchers alike. Prior to the Great Recession, there was a historic run-up in household debt, driven primarily by housing debt, which coincided with a speculative bubble and sharp rises in home prices. Then, as prices began to fall, millions of households began defaulting on their mortgages, unable to keep up with home payments, and greatly contributing to the onset of the deepest recession since the 1930s. Following the steep increase in debt balances during the boom, households began rapidly paying off their loans during and immediately after the Great Recession. Since 2013, debt has begun to increase and eventually rise above its previous levels, albeit at a much slower rate than before, at least partially owing to stricter lending standards. We examine the trends in household debt before, during, and since the 2000s financial crisis and Great Recession. As we will show, this period is unique in American history in several ways. Our analysis will show the sources of the historic run-up in debt during the bubble period of the early 2000s, the change in borrowing behavior that took place as the financial crisis and Great Recession took hold, and the nature of the recovery that began in 2013. We find that while total household debt has recovered to its previous level in nominal terms, its composition and characteristics have changed dramatically along many dimensions.
Keywords: D12; G01; G21; 330; household finance; consumer; debt